2008
DOI: 10.1063/1.2829818
|View full text |Cite
|
Sign up to set email alerts
|

A model for self-defocusing in laser drilling of polymeric materials

Abstract: A numerical thermal model is presented for laser microvias drilling in multilayer electronic substrates with Nd:YAG ͑YAG denotes yttrium aluminum garnet͒ and CO 2 lasers. Such substrates have different optical properties such as the refractive index and absorption coefficient at these two laser wavelengths, resulting in different drilling mechanisms. Since the skin depth of the polymer is large for both the lasers, volumetric heating is considered in the model. As soon as a small cavity is formed during the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The calculation results based on eqn [43] and eqn [44] are shown in Figure 39 and Figure 40, respectively. The comparison shows that the effect of non-Fourier heat conduction cannot be ignored.…”
Section: Main Theoretical Results Of the Thermodynamics Of Long-pulsementioning
confidence: 99%
See 1 more Smart Citation
“…The calculation results based on eqn [43] and eqn [44] are shown in Figure 39 and Figure 40, respectively. The comparison shows that the effect of non-Fourier heat conduction cannot be ignored.…”
Section: Main Theoretical Results Of the Thermodynamics Of Long-pulsementioning
confidence: 99%
“…However, for polymers, phase transitions (e.g., solid / melt / vapor) and chemical degradation often occur at high temperatures (39). Generally, both polymers and ceramics have a deeper heat penetration, so the heat transport theoretical model considering a volumetric heating for drilling is more accurate than a model only considering surface heating (41)(42)(43). Lawrence et al confirmed that for CO 2 laser, the absorption length for Al 2 O 3 /SiO 2 -based refractory material is three orders of magnitude greater than most of metals (38,40).…”
Section: Laser Drilling and Cuttingmentioning
confidence: 99%
“…The area of microwave drilling on various materials like concrete, glass, ceramics, basalts, silicon, and bones are well envisaged and explored [9] - [12]. The application of bone drilling in biomedical engineering, electronics industry and aeronautical engineering involves the majority of recent drilling applications for small size holes [13] - [18].…”
Section: Introductionmentioning
confidence: 99%